1998
DOI: 10.1002/(sici)1096-8628(19981204)80:4<343::aid-ajmg8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of Gaucher disease patients from Argentina: High prevalence of the RecNciI mutation

Abstract: Gaucher disease (GD) is caused by a deficiency of beta-glucocerebrosidase activity mainly due to mutations in the gene coding for the enzyme. More than 100 mutations have been identified to date and their frequencies have been established in several populations, including Ashkenazi Jews, among whom the disease is particularly prevalent. In order to study the molecular pathology of the disease in patients from Argentina, we conducted a systematic search for mutations in the glucocerebrosidase gene. Genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
2
15
2
1
Order By: Relevance
“…Since some patients may have A456P and lack the silent mutation in V460V, the frequency of RECs in this sample may be even higher. The high frequency of RECs was also described in other countries (9,15). It is generally observed that the RECs have a more severe impact on clinical manifestation than L444P alone (9,(16)(17)(18).…”
Section: Frequency Of the Most Common Mutationsmentioning
confidence: 61%
“…Since some patients may have A456P and lack the silent mutation in V460V, the frequency of RECs in this sample may be even higher. The high frequency of RECs was also described in other countries (9,15). It is generally observed that the RECs have a more severe impact on clinical manifestation than L444P alone (9,(16)(17)(18).…”
Section: Frequency Of the Most Common Mutationsmentioning
confidence: 61%
“…However, the frequency of Rec alleles in other studies ranged from 3.5% to 21%. [9,13,17] In addition to different ethnicity and sample size, technical differences may explain this variation. [16] Mutation analysis was done in some studies [9] by screening for the most common mutations only by the mismatched PCR amplifi cation technique, which has inherent limitations as additional mutations may result in under-estimation of the frequency of recombinant alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of GBA mutations are missense and non-sense, GBA recombinant alleles have been found at a high frequency in several populations (B24%), [12][13][14][15] but, are very rare in an Ashkenazi Jewish population (B3%). 12,13 In this study, we identified four recombinant alleles among 72 alleles (5.6%) of 36 unrelated Korean GD patients.…”
Section: Resultsmentioning
confidence: 99%